PENINGKATAN MENGENAL HURUF HIJAIYAH MELALUI MEDIA KARTU HURUF (Penelitian Tindakan pada Anak Usia 5-6 Tahun di PAUD Assa’dah Serang-Banten) - Mutia Nanda Herlina; atin fatimah; Fahmi Fahmi (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2018)
The purpose of this research is; 1) to know the process of card case media implementation can improve the recognition of the letters hijaiyah children aged 5-6 years in early childhood Assa’dah, and 2) to improve the recognition of letters hijaiyah children aged 5-6 years in early childhood Assa’dah can be improved through the media card alphabet. The method in this research is classroom action research method, in this research is children aged 5-6 years in PAUD Assa’dah Serang-Banten with amount of 10 child. This classroom action research procedure uses the Kemmis and Mc-Martgart model consisting of 3 stages: planning, action and observation, reflection. The process of collecting data is done through observation, field notes, interview notes and documentation notes. Data analysis uses data reduction, data presentation and conclusion. The results of this study are known that: 1) in the restudy ability to recognize the letters hijaiyah 32%, 2) after the child is given action on cycle 1, the ability to recognize the letters hijaiyah children increased to 51%, 3) in the second cycle obtained 77% results. Thus, the introduction of the hijaiyah letters of children has increased and is at a very good developing stage. It can be concluded that through the media card letters can improve recognize the letters hijaiyah children aged 5-6 years in PAUD Assa’dah Serang-Banten.